Optimisation of Cobalt Loading on γ-Al2O3 for Total Oxidation of Methane - Kumar M.; Rattan G.; Prasad R. (My University, 2025)
A series of Co/γ-Al2O3 catalysts with different Co (5–30 wt. %) loading were tested for methane oxidation. The catalysts were prepared by deposition precipitation method and calcined at 600°C for 4 h. The prepared samples were characterised by TGA, XRD. Among all the studied catalyst, Co (18 wt.%)/ γ-Al2O3 showed the highest activity for complete oxidation of methane at a temperature of 490°C. The catalytic activity of the tested samples follows Co (18 > 19 > 20 > 21 > 17 > 15 > 25 > 10 > 30 wt. %)/γ-Al2O3. The catalytic behaviour of these samples towards CH4 oxidation was found to increase with cobalt loading, though a plateau was reached at concentration of 18 wt. % Co content. It was observed that when cobalt (with the concentration of 18%) is supported on γ-alumina, it acts as a highly active catalyst for methane oxidation. However, with further increase in the cobalt contents on γ-alumina, the catalytic activity decreases. The oxidation of methane was carried out in a tubular fixed-bed reactor. A fixed weight (500 mg) of the catalyst was taken and 1.5% CH4 (1.5 mL/min) in air (148.5 mL/min) at a total feed rate of 150 mL/min was used in the reactor. © 2016 Indian Institute of Chemical Engineers.